Geography Learning Design Based on Spatial Phenomenon to Improve Higher-Order Thinking Skills - Utomo, Dwiyono Hari; Putri, Anita Eka (Sumatra Journal of Disaster, Geography and Geography Education, 2019)
Teaching material organizations must build higher-order thinking skills. This research is based on development research. Development research is oriented to the needs of the student through initial research to determine the design. Design of teaching materials including material organizations with formats based on the A-CAR model (Activation, Confirmation, Activities, and Resumes). The purpose of the research is to produce Meteorology-Climatology teaching material that can build higher-order thinking skills. This activity makes students compare weather or climate phenomena in different spaces. Design of validated teaching materials (content and language) is implemented in the teaching process. Revisions are based on input and experimental implementation. The results of the t-test analysis showed a significant effect on higher-order thinking skills.